THE GENIUS WHO CHANGED FAXRUDDIN ROZI’S WORLDVIEW - Boltaev A. A. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article examines the letter of the great mystic, scholar and sufi Muhyiddin ibn Arabi, who lived and worked in the XII-XIII centuries, to Fakhruddin Razi, the great scholar of kalam, sharia and tafsir(explanation of Qur’an) at that time, urging him to acquire the divine sciences.